Proceedings of the 2016 CHI Conference on Human Factors in Computing Systems 2016
DOI: 10.1145/2858036.2858333
|View full text |Cite
|
Sign up to set email alerts
|

The Social Media Ecology

Abstract: Many existing studies of social media focus on only one platform, but the reality of users' lived experiences is that most users incorporate multiple platforms into their communication practices in order to access the people and networks they desire to influence. In order to better understand how people make sharing decisions across multiple sites, we asked our participants (N=29) to categorize all modes of communication they used, with the goal of surfacing their mental models about managing sharing across pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 109 publications
(35 citation statements)
references
References 47 publications
1
34
0
Order By: Relevance
“…Thus, instead of segmenting networks on one SNS, people often separate their networks by using different social media sites for different networks and purposes, as I have shown in this study, and as others have found [81,98]. Such separations are not necessary for every context; if a person wants to post different content for their gym friends vs. their co-workers, Facebook lists may work fine.…”
Section: The Importance Of Social Media Site Separationmentioning
confidence: 83%
“…Thus, instead of segmenting networks on one SNS, people often separate their networks by using different social media sites for different networks and purposes, as I have shown in this study, and as others have found [81,98]. Such separations are not necessary for every context; if a person wants to post different content for their gym friends vs. their co-workers, Facebook lists may work fine.…”
Section: The Importance Of Social Media Site Separationmentioning
confidence: 83%
“…Through an interview study Zhao et al revealed how people considered both content and audience simultaneously as they decided which platform to use. They also showed how each individual contrasted their own "communication ecosystem" [4], indicating careful consideration of platforms' advantages and disadvantages. Semaan et al conducted a qualitative study of social media use for political deliberation and found that their participants purposefully used multiple platforms to obtain diverse political information and engage in respectful and reasoned discussions with different people [5].…”
Section: Social Media Activity and Online Contextsmentioning
confidence: 99%
“…For instance, managing social lives online is a complex endeavor due to context collapse [43], decisions around disclosure [2], and potential harassment [11]. Thus, many people maintain online identities and networks across several social media sites [18,40,44]. [22].…”
Section: Introductionmentioning
confidence: 99%